AN ANALYSIS OF PAUSE AND SLIP OF THE TONGUE IN ENGLISH EDUCATION STUDENTS OF UNMA BANTEN - KHOERUNNISA, SITI ALNIDA; GUMELAR, RIZDKI ELANG; ROHIMAJAYA, NUR AZMI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Speech errors can happen to everyone in every activity. This is inseparable from the world of education, one of which is microteaching activities. In its implementation in the English Education Study Program at Mathla'ul Anwar University Banten, there were several pauses and slips of the tongue that occurred. This research uses a qualitative approach. This research method is descriptive-qualitative. The data collection methods in this study involved observation, documentation, and checklists. In this study, the researchers conducted an obtrusive study by contacting several subjects and making observations to obtain data according to the formulation of the problem. The visual form of documentation that is the source of data is the microteaching video of sixth semester students of the English Education Study Program at Mathla'ul Anwar University Banten one video for one academic year, start from the 2019/2020 academic year to the 2022/2023 academic year. The results showed that all data, namely Subject A1 to Subject D1, had both types of pauses based on Fromkin's theory, namely silent pauses and filled pauses. While there are only 3 out of 6 types of tongue slips based on Dardjowidjojo theory, there are anticipation, transposition, and perseveration. While there is no slip of the tongue for the types of blend, malapropism, and substitution. In this research, speech errors such as pauses and slips of the tongue were caused by fatigue, a focus on accents, not mastering the material or vocabulary, nervousness, rushed, and the habit of saying the words “eee” and “aaa”. This finding also expects other researchers to further analyze psycholinguistics so as to minimize other speech errors.